Surgical management of superior sulcus tumors: A twenty-year experience of an oncological high volume referral centre - Bertolaccini, Luca; Casiraghi, Monica; Galetta, Domenico; Petrella, Francesco; Mazzella, Antonio; Lo Iacono, Giorgio; Girelli, Lara; Bardoni, Claudia; Mohamed, Shehab; Musso, Valeria; Sedda, Giulia; Spaggiari, Lorenzo (Frontiers in Oncology, 2023)
OBJECTIVES. Superior sulcus tumour, which affects the lung's apex, is an uncommon subtype of non-small cell lung cancer (NSCLC). The current study examined the clinical characteristics and management of superior sulcus NSCLC patients in a high-volume referral oncological centre over 22 years. METHODS. Retrospective review of 100 surgeries with curative intent for superior sulcus NSCLC over 22 years (July 1998 – December 2020). The surgical approach was defined according to the lesion site and the anatomy of the thoracic inlet. Survival curves, including non–cancer-related deaths, were drawn using the Kaplan-Meier methods, and the log-rank test was used to evaluate differences in survival across groups of patients. Cox proportional hazards regression was used to assess the association between selected clinical and pathologic characteristics on OS. RESULTS. 54 patients received induction treatments. The surgical approach was anterior thoracotomy in 53 patients, Paulson incision in 30, and a combined in 8. The median postoperative length of stay was 11 days (range: 5 – 27 days). Overall 90-day mortality was 6.93%. The median OS was 24.3 months. After a median follow-up of 3 years, 5-year and 10-year OS rates were 33.9% and 26.4%, respectively. A significantly lower 5-year OS was observed in patients with nodal disease (46.6% in pN0 vs 13.2% in pN+; p = 0.024), without preoperative treatments (41.0% in patients without preoperative treatments versus 17.4%; p = 0.09) and anteriorly located tumour (anterior vs posterior: 17.4% vs 49.1%; p = 0.032). Cox proportional hazards regression showed a better survival in pT1 stage (HR = 4.6; 95% CI: 1.9 – 11.2; p = 0.00076) and in R0 (HR = 4.2; 95% CI: 1.4 – 12.5; p = 0.010). CONCLUSIONS. Superior sulcus tumours still represent a life-threatening condition that, while curable in a significant proportion of cases, requires complex procedures with high surgical risks and a multimodality treatment setting. An optimal surgical approach should be planned to maximise resection completeness and survival. Other factors affecting survival are related to tumour staging, emphasising the importance of a meticulous preoperative workup and candidate selection to identify those expected to benefit from a survival benefit.